Fools of fortune - Trevor, William 1928-2016 (Penguin Books, 1984)
Willie Quinton, a child of eight, is becoming acutely aware that his Protestant parents are supporters of Irish Home Rule. His father and sisters are killed, but Willie surpresses the memory of their deaths until he grows up and falls in love with his English cousin Marianne.
Keywords: Skønlitteratur-Irland